2015
DOI: 10.1002/pc.23534
|View full text |Cite
|
Sign up to set email alerts
|

Properties of biodegradable thermoplastic cassava starch/sodium alginate composites prepared from injection molding

Abstract: Due to poor mechanical properties and high water uptake of biodegradable thermoplastic starch (TPS), in this study, the influence of sodium alginate on properties of biopolymer based on thermoplastic cassava starch (TPCS) was investigated. The TPCS polymer was compounded and shaped using an internal mixer and injection molding machine, respectively. In addition, the TPCS polymer was, then, modified by different contents of sodium alginate, i.e., 0, 10, 20, and 30 wt%. It was found that the TPCS composites show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…Calculating from the linear model, most of the alginate beads (>98%) will be degraded within half a year, which is a relatively rapid rate for soil biodegradation in general and a moderate rate for alginate degradation, which can be an advantage for slow‐release agricultural practices. Previous studies on soil degradation of alginate films or beads by weighing showed faster degradation, but the weighing technique disregarded that part of the weight lost due to breaking of the polymer as opposed to mineralization by microorganisms. Methane and hydrogen were also measured continuously as these gases represent additional microbial‐degradation pathways, and methane, being a potent greenhouse gas, is of particular environmental importance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculating from the linear model, most of the alginate beads (>98%) will be degraded within half a year, which is a relatively rapid rate for soil biodegradation in general and a moderate rate for alginate degradation, which can be an advantage for slow‐release agricultural practices. Previous studies on soil degradation of alginate films or beads by weighing showed faster degradation, but the weighing technique disregarded that part of the weight lost due to breaking of the polymer as opposed to mineralization by microorganisms. Methane and hydrogen were also measured continuously as these gases represent additional microbial‐degradation pathways, and methane, being a potent greenhouse gas, is of particular environmental importance.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from the results in this study, by measuring the respiration rate, more knowledge can be gained regarding the way in which, and the rate at which the alginate beads are degrading. Recent studies on alginate soil degradation have not looked at the kinetics or the rates at which alginate polymers (either beads or films) are degraded . Using either visualization of volume reduction or the VS technique, it is difficult to identify patterns and rates of degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPS polymers from several types of starch have been studied, i.e. corn [4], cassava [5], wheat [6], rice [7] and maize starch [8]. However, all TPS prepared from various sources of starch still show low mechanical properties and high hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, most of these textile sizing agents are derived from nonbiodegradable PVA. Thus, based on the need of environmental protection and sustainable development strategies, green biodegradable polymers have become increasingly popular as biodegradable polymers have great prospects and they can meet the requirements of environmental protection . Starch is a kind of biodegradable polymers that can be obtained from many renewable resources.…”
Section: Introductionmentioning
confidence: 99%